Biolaw, Digital Hyperconsuption and Cognitive Vulnerability: Towards a Biojuridical Resignification of Bioethical Principles for the Protection of Cognitive Health (Revista Justiça do Direito, 2022)
Cognitive health is necessary for human development. However, the hyperconsumption of biotechnologies (smartphones, internet, video games, social networks, virtual reality) can cause damage to cognitive health and, therefore, to human health and development. Consequently, such research focuses on limiting the consumption of specific technologies in minors in order to protect their health. This research is divided in five parts: the contextualization on the colonization of biotechnological consumption; a diagnosis of neuronal violence and consequences for human development; a review of the cognition sequelae due to the abuse of biotechnologies, based on selected medical research; an exposition on the necessary relationships between the moral order and the legal one, from philosophical realism and natural law approaches; proposal of minimum fundamental rules, based, in turn, on a biojuridical specification of principles to protect cognitive health, which serve as preliminary support to elaborate a future Universal Declaration for the Protection of Cognitive Health, as an essential biological basis for human development.